2010
DOI: 10.1002/jcop.20367
|View full text |Cite|
|
Sign up to set email alerts
|

Neighborhood context and the development of aggression in boys and girls

Abstract: We examine the roles of neighborhood characteristics in the development of the aggressive behavior of 1,409 urban boys and girls between the first and seventh grades. The multilevel, longitudinal growth analyses find strong neighborhood effects in all models, while controlling for individual-level variables. Results indicated that the effects of neighborhood violence, employment, income, and percentages of single males and female-headed households do not manifest in first grade, but affect the trajectory of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The income finding is consistent with literature that suggests that neighborhood poverty is associated with delinquency in general, and aggressiveness in particular (Leventhal and Brooks-Gunn 2000). Recent research suggests that factors such as neighborhood income become important for predicting aggressive behavior as children enter middle school (Vanfossen, Brown, Kellam, Sokoloff, and Doering 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The income finding is consistent with literature that suggests that neighborhood poverty is associated with delinquency in general, and aggressiveness in particular (Leventhal and Brooks-Gunn 2000). Recent research suggests that factors such as neighborhood income become important for predicting aggressive behavior as children enter middle school (Vanfossen, Brown, Kellam, Sokoloff, and Doering 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Further, stressors and frustrations associated with living in socioeconomically disadvantaged areas may prompt youth to act out in both physically and socially aggressive ways. In fact, neighborhood disadvantage has been found to predict trajectories of adolescent aggression, with higher initial levels (Karriker-Jaffe et al 2009), greater increases over time (Vanfossen et al 2010), and greater persistence of aggression into young adulthood (Howell and Hawkins 1998) in socioeconomically disadvantaged neighborhoods. Other than the study by Vanfossen and colleagues (2010), which used a composite measure of both physically and socially aggressive behaviors, we are unaware of other work that has examined neighborhood effects on social aggression.…”
Section: Study Overviewmentioning
confidence: 99%
“…Lack of social cohesion and informal control can lead to socially disordered neighborhoods that allow more unchecked aggression by adolescents living in them. Studies show increases in youth aggression over time (Vanfossen et al 2010), as well as persistence of aggression into young adulthood among youth in disorganized neighborhoods (Chung et al 2002). However, some research suggests limited effects of connection to neighbors on problem behaviors (including violence, delinquency and substance use) for rural African-American youth (Vazsonyi et al 2008).…”
Section: Study Overviewmentioning
confidence: 99%
“…In sum, previous research supports an association of NSSI with violent behaviour toward others and suggests the presence of a subgroup of individuals who engage in NSSI that also engage in violence (Hillbrand, 2001;Maden et al, 2000;Daffern & Howells, 2009 (Chermack et al, 2000;Cunradi et al, 2002;Vanfossen et al, 2010) and academic achievement (Hoptman et al, 1999;Farrington, 1989;Swahn & Donovan, 2004), as well as relationship (Saunders, 1992;Webster et al, 1997) and employment (Gatti et al, 2007;Zagar et al, 2009;O'Leary et al, 2008) difficulties have been associated with violent behaviour. In terms of individual factors, previous work has found that ASPD features are associated with violent or aggressive behaviour toward others (Meloy, 1995), and some authors have suggested an association between antisocial personality features and NSSI behaviours (Virkkunen, 1976).…”
Section: Discussionmentioning
confidence: 78%
“…another study examining aggression among elementary school boys and girls found that family income was associated with aggression in the first grade and that the neighbourhood factors, including the economic status of the neighbourhood, were associated with the pattern of aggressive behaviours over time for both males and females (Vanfossen, Brown, Kellam, Sokoloff, & Doering, 2010).…”
Section: Contextual Factorsmentioning
confidence: 98%